RELIGIOUS-SCIENTIFIC INSTITUTIONS IN KIRKUK IN THE LATE OTTOMAN ERA: A HISTORICAL DOCUMENTARY STUDY - Younis, Majid (Humanities Journal of University of Zakho, 2024)
The southern region of Kurdistan was among the first geographical areas to embrace Islam following its emergence in the early 7th century CE. With the arrival of the new religion in this part of Kurdistan, mosques began to appear, as they served as the cornerstone and starting point for spreading the principles of Islam. Gradually, mosques were built across Kurdistan, and their religious, scientific, and cultural significance grew in parallel with human development, the construction of villages and cities, and the increasing population. These Kurdish mosques and religious institutions gained a distinguished scholarly status within the Kurdish community from that period until the advent of modern history and the collapse of the Ottoman Empire at the end of World War I. Subsequently, with the rise of modern educational institutions, the scientific role of religious institutions diminished to some extent.This study explores the most significant mosques, religious schools, and Sufi lodges (takaya) in the Sanjak of Kirkuk during the late Ottoman period, based on documentary information from the Waqf registers of the Mosul province, of which Kirkuk was administratively a part. The research discusses the historical information provided in these sources, shedding light on modern Kurdish history during the late Ottoman era, particularly in terms of scientific and social aspects. The study also highlights the notable scholars of the Sanjak of Kirkuk and the key scholarly contributions of these mosques and religious institutions. Furthermore, it examines the endowments, both movable and immovable, dedicated by various individuals to some of these religious institutions. The research also delves into the administrative complexities that emerge during the study, and elucidates the nature of the relationship between the Ottoman state and the people of Kirkuk through these religious institutions, as well as the extent to which the Ottomans fulfilled their obligations towards the imams, scholars, and mosques of Kirkuk, given their role as the ruling authority in Iraq at that time.